Rhetorical Devices Used by Mark Zuckerberg in His 2007 Harvard Commencement Speech - Calvin Lauw; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This research analyzed the rhetorical devices used by Mark Zuckerberg in his 2007 Harvard commencement speech. The findings show Mark Zuckerberg’s speech used six out of eleven rhetorical devices in figurative language such as simile, catachresis, synecdoche, personification, allusion, and transferred epithet. The most frequent rhetorical device he used is catachresis. The other frequent rhetorical device he used is the transferred epithet. The least used of rhetorical devices in his speech simile, personification and synecdoche. From the findings, the writer concludes the rhetorical devices as the language method to improve the speaker's ability in delivering speech. Rhetorical devices affect in a positive way to improve the speaker's communication skill. The present research has some limited scope, which was based on a Mark Zuckerberg speech, further research would need to improve the knowledge about function and the use of rhetorical devices in a speech. The other research using different types of speech would also be recommended.